Puding Rumput Laut (Eucheuma cottonii) dan Kadar Glukosa Darah Postprandial - Nafisah, Afifatun; Isnawati, Muflihah; Sulistyowati, Enik (Poltekkes Kemenkes Semarang, 2014)
Background : Eucheuma cottonii is seaweed containing carrageenan, soluble fiber compounds. Carrageenan could affect the absorption of monosaccharides and delaythe rate of increasing blood glucose levels. This study aims to determine the effect of Eucheuma cottonii seaweed pudding on postprandial blood glucose levels.Method : Study design was an experimental series, involving 10 students of Polytechnic of Health Semarang, based on the inclusion criteria. The subjects received two kinds of interventions. Firstly, subjects received complete meals. In the next week, was treated with complete meal plus Eucheuma cottonii seaweed pudding. Paired T-test was used to analyze differences of postprandial blood glucose levels.Results : Mean levels of fasting and postprandial blood glucose after complete meal is 92.5 mg / dl, minute-30 was 133 mg / dl, 1st hour was 118.5 mg / dl, 2nd hours was 107.2 mg / dl and 3rd hour 95.8 mg / dl, respectively. Blood glucose level after complete meal plus 100 gram seaweed pudding, is 87.7 mg / dl, postprandial 30 minute 120.9 mg / dl, 1st hour 112.9 mg / dl, 2nd hour 104 mg / dl and 3rd hour of 95.4 mg / dl. There is no significant difference on post-prandial blood glucose after fed with Eucheuma cottonii puding (p 0.05).Conclusion : Eucheuma cottonii seaweed pudding does not affect postprandial blood glucose levels on healthy subjects.